Accelerated Amyloid Beta Pathogenesis by Bacterial Amyloid FapC. Issue 18 (16th July 2020) - Javed, Ibrahim; Zhang, Zhenzhen; Adamcik, Jozef; Andrikopoulos, Nicholas; Li, Yuhuan; Otzen, Daniel E.; Lin, Sijie; Mezzenga, Raffaele; Davis, Thomas P.; Ding, Feng; Ke, Pu Chun
Abstract: The gut–brain axis has attracted increasing attention in recent years, fueled by accumulating symptomatic, physiological, and pathological findings. In this study, the aggregation and toxicity of amyloid beta (A β ), the pathogenic peptide associated with Alzheimer's disease (AD), seeded by FapC amyloid fragments (FapCS) of Pseudomonas aeruginosa that colonizes the gut microbiome through infections are examined. FapCS display favorable binding with A β and a catalytic capacity in seeding the peptide amyloidosis. Upon seeding, twisted A β fibrils assume a much‐shortened periodicity approximating that of FapC fibrils, accompanied by a 37% sharp rise in the fibrillar diameter, compared with the control. The robust seeding capacity for A β by FapCS and the biofilm fragments derived from P. aeruginosa entail abnormal behavior pathology and immunohistology, as well as impaired cognitive function of zebrafish. Together, the data offer the first concrete evidence of structural integration and inheritance in peptide cross‐seeding, a crucial knowledge gap in understanding the pathological correlations between different amyloid diseases. The catalytic role of infectious bacteria in promoting A β amyloidosis may be exploited as a potential therapeutic target, while the altered mesoscopic signatures of A β fibrils may serve as a prototype for molecular assembly and a biomarker for screening bacterial infections in AD. Abstract : This study reveals a direct cross‐seeding linkage between bacterial amyloid protein FapC seeds and elevated A β fibrillization in vitro and in silico, and demonstrates the effects of such cross‐seeding on A β ‐elicited neurotoxicity and Alzheimer's‐like pathology in a zebrafish model. This study points to the role of infectious bacteria in mediating brain health.